An Icosidodecahedral Supramolecule Based on Pentaphosphaferrocene: From a Disordered Average Structure to Individual Isomers. Issue 43 (18th September 2017) - Heindl, Claudia; Peresypkina, Eugenia; Virovets, Alexander V.; Bushmarinov, Ivan S.; Medvedev, Michael G.; Krämer, Barbara; Dittrich, Birger; Scheer, Manfred
Abstract: Pentaphosphaferrocenes [Cp R Fe(η 5 ‐P5 )] (1 ) and Cu I halides are excellent building blocks for the formation of discrete supramolecules. Herein, we demonstrate the potential of Cu(CF3 SO3 ) for the construction of the novel 2D polymer [{Cp*Fe(μ4, η 5:1:1:1 ‐P5 )}{Cu(CF3 SO3 )}]n (2 ) and the unprecedented nanosphere (CH2 Cl2 )1.4 @[{Cp Bn Fe(η 5 ‐P5 )}12 {Cu(CF3 SO3 )}19.6 ] (3 ). The supramolecule3 has a unique scaffold beyond the fullerene topology, with 20 copper atoms statistically distributed over the 30 vertices of an icosidodecahedron. Combinatorics was used to interpret the average disordered structure of the supramolecules. In this case, only two pairs of enantiomers with D5 and D2 symmetry are possible for bidentate bridging coordination of the triflate ligands. DFT calculations showed that differences in the energies of the isomers are negligible. The benzyl ligands enhance the solubility of3, enabling NMR‐spectroscopic and mass‐spectrometric investigations. Abstract : With the CF3 SO3 − anion as a spacer, a new type of giant supramolecule was obtained from pentaphosphaferrocene and Cu + . With 20 copper atoms distributed over the 30 vertices of a giant icosidodecahedron, its unprecedented scaffold contains intrinsic vacancies and exists as four isomers.